How Chinese SMEs Innovate Using 'Diegetic Innovation Templating' – The stimulating role of Sci-Fi and fantasy. (January 2018) - Zheng, Ping; Callaghan, Victor
Highlights: Diegetic Innovation Templates (DiT) provides a novel instrument for new product/process development in organisations. The Diegetic Gap (DiG) metric is introduced to aid understanding of the connections between the fiction and the reality. General cultural products, particularly science fiction and fantasy can simulate innovation outcomes in organisations. The transformation process from fiction to real product is multi-dimensional which can enhance innovation capability. Enabling conditions for the use of DiT and DiG in product innovation are identified. Abstract: Use of established fiction provides a connection to society at large, tapping into the creative abilities of great authors and filmmakers, which can offer a valuable source of creative ideas. This paper explores how science fiction and fantasy, particularly in the form of films, is being used to stimulate creativity and produce innovation outputs in non-science SMEs in China. We argue that fiction has the potential to inspire innovation through a constructive organisational process, we provide a simple metric, the ' Diegetic Gap ', as a means for illustrating this. In particular, we present four empirical case studies that explore the application of science fiction and fantasy to product and process innovation, utilising a concept we call a Diegetic Innovation Template to merge fictional narrative and tangible innovation output.